Implementation of Green Human Resource Management for MSMEs in Indonesia: A Review - Alfianto, Rahmad; Firdausi, Emir Rifky; Andriyani, Andriyani (LifeSciFi, 2024)
Indonesia has responsibility for promoting a green economy, in which Micro, Small, and Medium Enterprises (MSMEs) are a contributor to the country's economy. In running a business, Green Human Resource Management (GHRM) has an important role for maintaining business sustainability in Indonesia. This study aims to review the implementation of GHRM for MSMEs in Indonesia. The research method used is a literature review on green human resource management for MSMEs in Indonesia from 16 articles collected through the Google Scholar database. The results of this study are that implementation of GHRM significantly enhance environmental performance and overall business sustainability. The application of GHRM to MSMEs in Indonesia covers various aspects, including green recruitment, green training and development, green performance, and green rewards. GHRM consistently demonstrates potential for fostering competitive advantage and innovation. Key practices such as green recruitment and training play crucial roles in promoting green work behaviors. Managerial implications emphasize the integration of green principles across HRM functions and leadership commitment to drive GHRM success.